2020
DOI: 10.33215/sjom.v3i5.421
|View full text |Cite
|
Sign up to set email alerts
|

Employee Empowerment and Innovative Work Behavior

Abstract: Purpose: This paper seeks to address the moderating effect of leader-member exchange on the link between employee empowerment and innovative work behavior. Design/Methodology: The study draws on the causal-comparative research design, and employs paper-based self-administered questionnaires to gather data from a sample of 470 employees drawn from manufacturing firms in Kenya. This sample is part of a population of 9915 employees and has been narrowed down using Yamane’s formula. The study employs stratified an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…By empowering employees, leaders enhance employees' sense of belonging and honor to the organization, making them psychologically grateful to the organization and giving back to the organization through performance. This is an effective strategy in which employees can make their own decisions and spark innovation (Kanake & Kemboi, 2020)…”
Section: Creativity and Empowermentmentioning
confidence: 99%
“…By empowering employees, leaders enhance employees' sense of belonging and honor to the organization, making them psychologically grateful to the organization and giving back to the organization through performance. This is an effective strategy in which employees can make their own decisions and spark innovation (Kanake & Kemboi, 2020)…”
Section: Creativity and Empowermentmentioning
confidence: 99%
“…Such a relationship results to a form of exchange between the leader and subordinates such that the subordinates respect and follow the leader willingly when they perceive a high-quality dyad (Adero & Odiyo, 2020;Kariuki, 2020;Northouse, 2016). The key proponents of this theory were Graen and Cashman in 1975, and Dansereau, Graen, and Haga in 1975. Kanake and Kemboi (2020 utilized this theory in their investigation of the relationship between employee empowerment and innovative work behaviour.…”
Section: Leader-member Exchange Theorymentioning
confidence: 99%
“…On the other hand, employees who possessed a low LMX with their supervisors felt less valued and were more inclined to quit the organization. Kanake and Kemboi (2020) used the theory to carry out a study investigating the relationship between employee empowerment and innovative work behaviour. The study revealed that the kind of exchange between the leaders and staff is positively moderated by the nature of the relationship between them.…”
Section: Leader-member Exchange Theorymentioning
confidence: 99%